Study Of Ashtaharavidhivisheshayatana: A Review - Mewal, Jyoti; Joshi, ,Dr. Shruti; Yadav, Chhaju Ram (International Research Journal of Ayurveda & Yoga, 2021)
Ayurveda is regarded as an important science of life. In Ayurveda, two Prayojana are mentioned - first one is to protect health of the healthy person and second is to cure disorder of the diseased person. Health is the supreme foundation for the achievements of long life. Foods which are consumed according to the prescribed methods are the seat for the satisfaction of life. Ahara is among the three supporting factors of life (Trayopstambha i.e., Ahara, Nidra & Brahmcharya) which plays a key role in sustenance and maintenance of life. In today’s era, altered dietary habits may lead to various types of diseases. For intake of Ahara or food, Ayurveda has mentioned some conditions which need to be followed to obtain complete benefits of food which are known as Ashtaharavidhivisheshayatana. These are termed as rules of intake of diet mentioned by Acharya Charaka in the first chapter of Vimana Sthana - ’Rasa Vimana’. Ahara means food, Vidhi means methodology and manners of food intake, Vishesha means peculiar and Ayatana means Hetu.